Chylous ascites caused by resection of a choledochal cyst - Tatsuzo Mizukami; Tadao Okada; Shohei Honda; Hisayuki Miyagi; Masashi Minato; Satoru Todo (Wolters Kluwer Medknow Publications, 2012)
Chylous ascites is a rare complication of abdominal surgery in children. Particularly, reports of postoperative chylous ascites are rare. This report describes the very rare case of a 10-month-old girl complicated by chylous ascites after resection of a choledochal cyst with a Roux-en-Y hepaticojejunostomy, who was successfully treated medically. To date, we have found a few cases of postoperative chylous ascites in the paediatric literature. To the best of our knowledge, this is the first report of chylous ascites after the resection of a choledochal cyst in a child who was successfully treated solely by no fasting. No fasting might be a therapeutic option of paediatric postoperative chylous ascites after the resection of a choledochal cyst if the outflow volume of chylous ascites is small.